Optimasi Pemupukan NPK pada Kedelai untuk Mempertahankan Kesuburan Tanah dan Hasil Tinggi di Lahan Sawah - Achmad Ghozi Manshuri (Iptek Tanaman Pangan, 2012)
Factors causing a low soybean productivity in Indonesia among the others is the inoptimum availability of nutrients. Report had indicated that the N, P, and K nutrients balance in soybean production centers of lowlands tend to be negative, caused by inbalance fertilization practices and habit of the farmers to take the entire crop harvest off the land. It was estimated that deficit at 45 to 50 kg N, 0 to 4 kg of P, and 0 to 30 kg K/ha happened when rice was harvested, crop yielded 6 t/ha in low land. From an average soybean yields of 1 t/ha, it took nutrient off the land of about 70 kg N, 7 kg P, and 43 kg K/ha. There is an indication the occurance of the hidden hunger symptoms of N and P in some farmers lands. Fertilization of N and P had increased grain yield, but the increase was not high enough to convince farmers. For that reason, usually N and P fertilization was not applied. Farmers also choose not to fertilize the soybean crop, because it is not profitable. The policy of not recommending fertilization on to the hidden hunger lands needs to be revised, because in the long run it will not beneficial for the sustainability of the soil fertility and productive farming. The principle of optimization of N, P, and K fertilization is to apply fertilizers as much as plants need to reach the targeted yield and to conserve the nutrient status in the soil. Thus, it could result in soybean yield increases and maintains soil fertility. The recommendation of N, P, and K optimization on soybean plants can be performed: 1) based on the analysis of the status of N, P, and K soil, 2) optimization of fertilization of N, P, and K based on the agronomic efficiency of N, P, and K.